2005
DOI: 10.1177/0741713605277372
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Directed Learning Process of Older, Rural Adults

Abstract: Medical advances and lifestyle changes have resulted in older adults living longer and healthier lives. Nevertheless, older adulthood, as other life stages, requires change in work, family, and health. Self-directed learning (SDL) is one way of negotiating these transitions. The purpose of this study was to understand this process of learning. This study employed a general qualitative design incorporating in-depth, semi-structured interviews for data collection. The sample of 10 purposefully selected adults fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 23 publications
3
51
1
3
Order By: Relevance
“…Qualitative methods have been recommended (Grant, 2001;Infantino, 2005;Shoemaker et al, 2000) because the focus on verbal or written dialogue facilitates a comparatively more in-depth and less constrained response. In addition, qualitative methods have been shown to be particularly effective in eliciting reflective responses from older adults on the subject of their health, well-being, and leisure (Cromby, 2012;Fee et al, 1999;Roberson & Merriam, 2005;Robertson & Hale, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative methods have been recommended (Grant, 2001;Infantino, 2005;Shoemaker et al, 2000) because the focus on verbal or written dialogue facilitates a comparatively more in-depth and less constrained response. In addition, qualitative methods have been shown to be particularly effective in eliciting reflective responses from older adults on the subject of their health, well-being, and leisure (Cromby, 2012;Fee et al, 1999;Roberson & Merriam, 2005;Robertson & Hale, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…El-Gilany y El Sayed 23 evidenciaron que no hay una variación significativa entre los antecedentes demográficos de los estudiantes y su desempeño académico. Sin embargo, Roberson y Merriam 24 sí identificaron relaciones entre la variable edad y sexo con el comportamiento de los estudiantes.…”
Section: Discussionunclassified
“…For example, Huang (2002) discussed instructional principles for guiding adult learning in online environments, and concluded that constructivist principles provide useful ideas to help educators create learner-centered and collaborative environments. Other studies have emphasised issues regarding inner motivation (Merriam, Caffarella, & Baumgartner, 2012), self-direction (Burge & Frewin, 2014;Kenner & Weinerman, 2011), flexibility (Bash, 2003;Eastmond, 1998), and the process of learning (Roberson & Merriam, 2005). Most importantly, they focus on the fact that instructors should recognise adults' learning needs, which may be different from those of children or traditional college students (Cercone, 2008).…”
Section: Adult Online Learningmentioning
confidence: 99%